Nutritional, medicinal, and performance enhancing supplementation in dance. Issue 1 (March 2016) - Boardley, Ian D.; Allen, Nick; Simmons, Alexander; Laws, Helen
Highlights: Use of at least one supplement was reported by 91.9% of dancers. Prevalence highest for multivitamins, OTC painkillers, and high energy drinks. Numerous forms of supplementation more prevalent in male and professional dancers. Physiotherapists and GPs/physicians considered important sources of information. Non-dance friends considered least important source of information. Abstract: The aims of the current study were to: (a) investigate the reported prevalence of nutritional, medicinal, and performance enhancing substance use in dance, including any gender or professional status differences, and (b) examine the amount of importance dancers place on potential sources of information regarding supplementation. Methods involved administering an anonymous survey to 371 male ( n = 83) and female ( n = 286) UK-based dancers ( M age = 20.87 years). Use of at least one supplement was reported by 91.9% of the dancers surveyed, and prevalence rates were highest for multivitamins, over-the-counter painkillers, and high energy drinks. Prevalence of use varied from low to high for specific nutritional and medicinal supplements, whereas very low levels of supplementation were seen for all performance enhancing supplements. Numerous forms of supplementation were more prevalent in male and professional dancers in comparison to female and amateur dancers, respectively. Across all categories of supplementation, physiotherapists and GPs/physicians were considered to be important sources of information on supplementation, whereas non-dance friends were considered to be the least important source of information. In conclusion, the current study provides much needed information on nutritional, medicinal and performance enhancing supplementation in dancers, and identifies key sources of information for dancers on all forms of supplementation.